Rehabilitation training robot using mirror therapy for the upper and lower limb after stroke: a prospective cohort study - Xixi Wu; Xu Qiao; Yudi Xie; Qingyan Yang; Wenting An; Lingfeng Xia; Jiatao Li; Xiao Lu (Journal of NeuroEngineering and Rehabilitation)
Abstract Background This prospective cohort study was designed to investigate and compare the effectiveness of rehabilitation training robots versus conventional rehabilitation training on stroke survivors by monitoring alterations in brain network of stroke patients before and after robot intervention. Methods Between September 2020 and November 2021, stroke patients at four grade-A tertiary hospitals underwent limb rehabilitation training. Of the total of participants, 117 patients received conventional limb rehabilitation, 93 patients participated in upper-limb robot training, and 103 patients underwent lower-limb robot training. The measured outcomes included modified Barthel Index (MBI), Fugl-Meyer assessment subscale (FMA), and manual muscle testing (MMT). Functional magnetic resonance imaging (fMRI) was conducted on 30 patients to assess changes in the brain network. Data were mainly analyzed based on the Intention-to-Treat (ITT) principle. Results Post-interventional analysis utilizing linear mixed models in ITT analysis revealed that the robot training group had greater enhancements compared to the conventional limb rehabilitation training group. Notably, the shoulder flexor strength (P = 0.043) was significantly higher in the upper-limb group. On the other hand, hip flexor strength (P < 0.001), hip extensor strength (P < 0.001), knee extensor strength (P = 0.013), ankle dorsiflexion strength (P < 0.001) and ankle plantarflexor strength (P < 0.001) were significantly higher in the lower-limb group. In the upper-limb group, region-of-interest (ROI) -to-ROI analysis revealed enhanced functional connectivity between the left hemisphere’s motor control region and the auditory network. ROI-to-ROI analysis primarily showed enhanced interhemispheric functional connectivity in the lower-limb group, specifically between right the hemisphere’s motor control region (central opercular cortex) and left hemisphere’s primary motor area in the precentral gyrus. Conclusions According to our research findings, upper- and lower-limb rehabilitation robots demonstrated great potential in promoting motor function recovery in stroke patients. Robot-assisted training offers an alternative treatment method with comparable efficacy to traditional rehabilitation. Large-scale randomized controlled trials are needed to confirm these results. Trial registration : The study was registered on the Chinese Clinical Trial Registry (ChiCTR1800019783).